Genetic Biofortification to Enrich Rice and Wheat Grain Iron: From Genes to Product - Ludwig, Yvonne; Slamet-Loedin, Inez H. (Frontiers in Plant Science, 2019)
The micronutrient iron (Fe) is not only essential for plant survival and proliferation but also crucial for healthy human growth and development. Rice and wheat are the two leading staples globally; unfortunately, popular rice and wheat cultivars only have a minuscule amount of Fe content and mainly present in the outer bran layers. Unavailability of considerable Fe-rich rice and wheat germplasms limit the potential of conventional breeding to develop this micronutrient trait in both staples. Agronomic biofortification, defined as soil and foliar fertilizer application, has potential but remains quite challenging to improve grain Fe to the significant level. In contrast, recent accomplishments in genetic biofortification can help to develop Fe-enriched cereal grains to sustainably address the problem of "hidden hunger" when the roadmap from proof of concept to product and adoption can be achieved. Here we highlight the different genetic biofortification strategies for rice and wheat and path to develop a product.